2014
DOI: 10.1007/s12013-014-9854-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Upper Cervical Spine Instability with Posterior Fusion Plus Atlantoaxial Pedicle Screw

Abstract: Clinical results of posterior fusion plus pedicle screw fixation in the treatment of upper cervical spine instability were taken under consideration. 24 patients with atlantoaxial instability were treated with C1-2 pedicle screws and rods fixation under general anesthesia. There were 18 males and 6 females with mean age of 49.8 years (age range 17-69 years). The postoperative radiographs verified good position of all screws, with satisfactory atlantoaxial reduction. Follow-up for 3-45 months (average 23 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Our prospective, self-controlled comparative study demonstrated the advantages of the C1 pedicle screw technique, as superior to the C1 lateral mass screw technique; including less blood loss, shorter operative times, and fewer postoperative complications [53]. Thus, the C1 pedicle screw technique has become the most popular C1 screw technique [48,52,[54][55][56]. Many strategies of C1 pedicle screw placement have been introduced [36][37][38]57,58].…”
Section: C1 Screw Techniques C1 Lateral Mass Screw Techniquementioning
confidence: 79%
“…Our prospective, self-controlled comparative study demonstrated the advantages of the C1 pedicle screw technique, as superior to the C1 lateral mass screw technique; including less blood loss, shorter operative times, and fewer postoperative complications [53]. Thus, the C1 pedicle screw technique has become the most popular C1 screw technique [48,52,[54][55][56]. Many strategies of C1 pedicle screw placement have been introduced [36][37][38]57,58].…”
Section: C1 Screw Techniques C1 Lateral Mass Screw Techniquementioning
confidence: 79%
“…Posterior cervical pedicle screw fixation was performed on all patients as described in previous studies [ 11 , 13 , 15 ]. After general anesthesia, the patient was placed in a prone position and a midline incision was made to expose the C1 to C3 spinous process and lamina and then the atlantoaxial joint.…”
Section: Methodsmentioning
confidence: 99%
“…Sufficient experience and complication management skills are mandatory to perform the operation safely. 32 Conversely, in cases in which nerve root decompression is clinically and radiologically required and not feasible via the mere anterior interbody access (thus requiring supplementary posterior dural exploration), the advantage of ALIF is reduced and can then be outweighed by the inherent risks of the approach as well as the longer operation time. The three patients of the ALIF group that required additional dorsal decompression were considered to benefit from the better bilateral foraminal height restoration and broad base fusion surface of ALIF, but a mere posterior approach might have shown similar results.…”
Section: Alif Versus Tlif Technique For Pdsmentioning
confidence: 99%